Design of Online Animal Histology Atlas as a Learning Source - Khasanah, Laela Umi; Pratiwi, Millati; Zahroh, Risti (Proceeding International Conference on Science and Engineering, 2019)
This study aims to (1) determine the structure of histology of various organ systems, (2) develop online animal histology atlas as a source of learning in high school/MA so as to facilitate students in studying animal tissue, (3) determine the quality of learning resources in the form of online animal histology atlas so worthy of being used as a learning resource for high school biology. Online animal histology atlas is made in several stages. First, photographing histology preparations at the Integrated Laboratory of UIN Sunan Kalijaga, UGM Animal Structure & Development Laboratory, and the Biology Laboratory of Kasihan State High School. Of the three laboratories, histology preparations were obtained from six organ systems, namely the nervous system, cardiovascular system, integumentary system, digestive system, respiratory system, and male and female reproductive systems. Second, design an online animal histology atlas website with HTML 5, CSS 3 and JavaScript programming languages, as well as with the help of Bootstrap framework, resulting in an online animal histology web atlas that has a responsive and attractive appearance. Online Atlas of Animal Histology was then tested on material experts, media experts, peer reviewers, biology teachers and students of MAN 3 Bantul. The results of online animal histology atlas quality assessment by material experts received a score of 90.7% with very good quality, 91.4% of media experts with very good quality, 90.47% peer reviewers with very good quality, biology teacher 87.43% with very good quality, and 84.7% students with very good quality. Thus, the quality of the online atlas entitled "Atlas of Animal Histology" with the address atlashistologi.com as a whole is very good quality and suitable for use as a learning resource.